Research on Transverse Restraint System of Cable-stayed Bridge under Ultra High Performance Concrete Deck Pavement. Issue 1 (1st January 2022) - Zhou, M; Liu, Y; Gao, M; Zhu, GQ
Abstract: In order to explore the optimal lateral restraint system for long-span cable-stayed bridges under ultra-high performance concrete deck pavement. This paper takes a UHPC deck pavement cable-stayed bridge as an example, selects four different lateral restraint systems, calculates the stress of each key section of the cable-stayed bridge under the action of an earthquake, and then selects the optimal lateral Constraint system. The research results show that when ultra-high performance concrete is used as the bridge deck pavement, the increase in the quality of the bridge deck system will have a greater adverse effect on the seismic performance of the bridge. Compare the internal force response and displacement response at each key section of the bridge under four different lateral restraint systems under earthquake action. Compared with the other three systems, the internal force response and displacement response value of the horizontal cable system is smaller, and the energy dissipation and shock absorption effect is better. For cable-stayed bridges using ultra-high performance concrete as the deck pavement, in the selection of the lateral restraint system, a restraint system of cables is set between the towers and beams, which can better reduce the impact of the increase in the quality of the bridge deck on the seismic performance of the bridge, is the most reasonable horizontal restraint method. Considering the internal force and displacement response of the bridge structure and the safety of the support under the earthquake, the parameter selection of the cable support is k = 135000 kN / m and S = 0.4 m.